The synthesis, characterization, and electrical conductivity of the potassium salt of 1,3-dipiperidin-1-ylpropan-2-O-xanthate - Yakuphanoğlu, Fahrettin; Görgülü, AO; Aydogdu, Y; Aydogdu, A; Arslan, M (Taylor & Francis Inc, 2003)
This paper presents the electrical and optical studies on the potassium salt of 1,3-dipiperidin-1-ylpropan-2-O-xanthate (1). Compound (1) was characterized by relevant spectroscopy (H-1 and C-13 NMR and IR) and elemental analyses). The dependence of the conductivity on the temperature of the compound was measured in the temperature range 270-330 K and it is seen that the conductivity of the compound (1) increases with increasing temperature. The optical band gap energy is determined by means of an optical absorption method. Its conductivity at room temperature, activation energy, and optical band gap were found to be 2.7 10(-7) S.cm(-1) E-a=0.42 eV, and E-g=1.74 eV, respectively. The activation energy and optical band gap were below 2 eV, which places them in the semiconductors regime. The obtained values for a semiconducting material are typical values. It is concluded that compound (1) shows semiconducting behaviour as its conductivity increases with an increase in the temperature.
Keywords: organic semiconductor; electrical conductivity; xanthate salt